2003
DOI: 10.1021/bi027418p
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Inhibition of Cdc25 Phosphatases by Vitamin K Analogues

Abstract: A synthetic K vitamin analogue, 2-(2-mercaptothenol)-3-methyl-1,4-naphthoquinone or Cpd 5, was previously found to be a potent inhibitor of cell growth [Nishikawa et al., (1995) J. Biol. Chem. 270, 28304-28310]. The mechanisms of cell growth were hypothesized to include the inactivation of cellular protein tyrosine phosphatases, especially the Cdc25 family [Tamura et al. (2000) Cancer Res. 60, 1317-1325]. In this study, we synthesized PD 49, a new biotin containing Cpd 5 derivative, to search for evidence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…We previously found that PD 49, a biotin-tagged derivative of Cpd 5, interacted with the catalytic site of Cdc25Bcat (20). We explored whether PD 49 and PM-20 might bind to the same catalytic domain in Cdc25Bcat.…”
Section: Binding and Inactivation Of Cdc25 Phosphatases In Cell-free mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that PD 49, a biotin-tagged derivative of Cpd 5, interacted with the catalytic site of Cdc25Bcat (20). We explored whether PD 49 and PM-20 might bind to the same catalytic domain in Cdc25Bcat.…”
Section: Binding and Inactivation Of Cdc25 Phosphatases In Cell-free mentioning
confidence: 99%
“…They especially antagonize the action of extracellular signal -regulated kinase (ERK) phosphatases, resulting in prolonged ERK phosphorylation (14 -19). One of these compounds, Cpd 5, was also found to bind to Cdc25 at its catalytic cysteine (20). Cpd 5 was also found to block hepatoma cell growth both in vitro and in vivo (16, 21 -23).…”
Section: Introductionmentioning
confidence: 99%
“…Of the multiple PTPs, PTP1B is ubiquitously expressed (20) and negatively regulates receptor tyrosine kinases such as EGFR (21), so that inhibition of this PTP would lead to EGFR activation. Although 1,2-and 1,4-NQ and their derivatives are reported to be potent inhibitors for PTP1B (22,23), their detailed mechanism of action still remains unclear. This report describes results of a study of 1,2-NQ-PTP1B interaction, which demonstrates that 1,2-NQ-mediated covalent modification of PTP1B, accompanied by reduction of its enzyme activity, results in the transactivation of EGFR in human epithelial A431 cells.…”
mentioning
confidence: 99%
“…Covalent addition [41,42] and irreversible oxidation [43] of cysteine in the active site are the main mechanisms. Since p-benzoquinone was contained in the structure of the three sesquiterpene quinones, the inhibition of dysidine against PTP1B was measured in the presence of either DTT (5 mmol/L) or catalase (1000 U/mL) to investigate whether these quinone-dependent mechanisms were involved.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a number of ortho-quinone-containing compounds inhibited PTPα in a catalase-sensitive manner [43] , suggesting that these compounds inhibited PTPα via generation of ROS (including H 2 O 2 ) and subsequent oxidation of cysteine in the active site. Moreover, menadione (vitamin K3) [41] and other vitamin K analogues [42] containing a benzoquinone in their structure were reported to inhibit the CDC25 phosphatase by covalent interaction between the compound and the enzyme. This covalent bond can be blocked by DTT, GSH or other thiol-containing reductants.…”
Section: Discussionmentioning
confidence: 99%